Influence of Hydrophilicity on the Thermal-Driven Surfactant Flow at the Air/Water Surface - Nguyen, T.; Phan, Chi (2018)
A series of Triton surfactants with increasing number of ethylene oxide (EO) groups were applied to investigate thermal-driven surface flow. It was found that the thermal gradient is proportional to the number of EO groups on the surface. This correlation leads to the linear correlation between the surfactant structure and the driving force of the surface flow. The friction force, in contrast, follows a monotonic but nonlinear correlation with surfactant's EO groups. The results demonstrate the possibilities to manipulate the surface flow, with potential applications in multiple-phase systems.